In the above diagram, □ A B C D is a square with side A D extended to point E , and B E is a straight line. If the length of B C is ∣ B C ∣ = a = 3 0 and ∣ C F ∣ = b = 2 0 , what is the area of △ C E F ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Since △ B F C ∼ △ D F E , we have
1 0 x = 2 0 3 0 ⟹ x = 2 0 3 0 0 = 1 5
A C E F = 4 5 ( 3 0 ) − 2 1 ( 4 5 ) ( 3 0 ) − 2 1 ( 3 0 ) ( 2 0 ) − 2 1 ( 3 0 ) ( 1 5 ) = 1 3 5 0 − 6 7 5 − 3 0 0 − 2 2 5 = 1 5 0
Note:
A(CEF) = A(BEC) - A(BFC) = 0.5(BC)(CD) - 0.5(BC)(FC) = 0.5(30)(30) - 0.5(30)(20) = 150
From the given information, we know that FD = 10, because CD = 30 and CF = 20 (subtraction).
We know that triangles FDE and BAE are similar, because both share angle DEF and are right triangles, and and DE and AB are parallel, so angles DFE and ABE are equal).
Therefore side 1/side 2 of triangle ABE = side 1/side 2 of triangle FDE, and let DE = x.
30/(30+x) = 10/x --> 30x = 300 + 10x --> 20x = 300 --> x = 15
By the triangle formula, 1/2bh, the area of CFE is (1/2)(20)(15) = 150.
Notice that
∠
A
E
B
=
∠
E
B
C
, so
B
C
F
C
=
A
E
A
B
⟹
3
0
2
0
=
A
E
3
0
or
A
E
=
4
5
Solving for the area of A C E F ,
A C E F = A A E C B − A A E B − A B C F = [ 2 1 ( 3 0 + 4 5 ) ( 3 0 ) ] − 2 1 ( 3 0 ) ( 4 5 ) − 2 1 ( 2 0 ) ( 3 0 ) = 1 5 0
Problem Loading...
Note Loading...
Set Loading...
Since A E is parallel to B C , ∠ F B C = ∠ F E D and ∠ F C B = ∠ F D E = 9 0 ∘ , implying △ F B C and △ F E D are similar triangles. Also, since ∣ B C ∣ = ∣ C D ∣ , we have ∣ D F ∣ = ∣ B C ∣ − ∣ C F ∣ = 3 0 − 2 0 = 1 0 . Hence, ∣ C F ∣ : ∣ D F ∣ 2 0 : 1 0 ∣ D E ∣ = ∣ B C ∣ : ∣ D E ∣ = 3 0 : ∣ D E ∣ = 1 5 .
Let ∣ △ C E F ∣ denote the area of △ C E F , and ∣ □ A B C E ∣ the area of □ A B C E . Then since ∣ △ C E F ∣ = ∣ □ A B C E ∣ − ( ∣ □ A B C D ∣ + ∣ △ D E F ∣ ) , we have Area of △ C E F = ∣ □ A B C E ∣ − ( ∣ □ A B C D ∣ + ∣ △ D E F ∣ ) = 2 1 × ∣ A B ∣ × ( ∣ B C ∣ + ∣ A E ∣ ) − ( ∣ B C ∣ 2 + 2 1 × ∣ D E ∣ × ∣ D F ∣ ) = 2 1 × 3 0 × ( 3 0 + 4 5 ) − ( 9 0 0 + 7 5 ) = 1 5 0 .